Systematic review of exercise training in colorectal cancer patients during treatment. (26th May 2017) - van Rooijen, S. J.; Engelen, M. A.; Scheede‐Bergdahl, C.; Carli, F.; Roumen, R. M. H.; Slooter, G. D.; Schep, G.
Abstract : Colorectal cancer surgery results in considerable postoperative morbidity, mortality and reduced quality of life. As many patients will undergo additional (neo)adjuvant therapy, it is imperative that each individual optimize their physical function. To elucidate the potential of exercise in patient optimization, we investigated the evidence for an exercise program before and after surgical treatment in colorectal cancer patients. A systematic review was conducted according to the Cochrane Handbook for Systematic Reviews of Interventions, the guidelines of the Physical Therapy Journal and the PRISMA guidelines. No literature pertaining to exercise training during preoperative neoadjuvant treatment was found. Seven studies, investigating the effects of regular exercise during adjuvant chemotherapy for patients with colorectal cancer or a mixed population, were identified. A small effect (effect size (ES) 0.4) of endurance/interval training and strength training (ES 0.4) was found in two studies conducted in patients with colorectal and gastrointestinal cancer. In five studies that included a mixed population of cancer patients, interval training resulted in a large improvement (ES 1.5; P ≤.05). Endurance training alone was found to increase both lower extremity strength and endurance capacity. The effects of strength training in the lower extremity are moderate, whereas, in the upper extremity, the increase is small. There is limited evidence available on exercise training during treatment in colorectal cancer patients. One study concluded exercise therapy may be beneficial for colorectal cancer patients during adjuvant treatment. The possible advantages of training during neoadjuvant treatment may be explored by prehabilitation trials.